Preoperative detection of sentinel lymph node in patients with endometrial cancer - comparison of planar lymphoscintigraphy, spect and SPECT/CT - Jankulovska, Anamarija; Stoilovska Rizova, Bojana; Bozhinovska, Nikolina; Peshevska, Aleksandra; Tanturovski, Mile; Aluloski, Igor; Stojchevski, Sasho; Manevska, Nevena; Stojanoski, Sinisha; Miladinova, Daniela (My University, 2022)
Sentinel lymph node (SLN) mapping allows minimal invasive assessment of lymph node status in patients with early-stage endometrial cancer (EC). Intraoperative detection of SLNs is based on the results obtained from preoperative nuclear medical images. The purpose of this study was to compare the data obtained from planar lymphoscintigraphy (PL), single-photon emission computed tomography (SPECT), and SPECT with computed tomography (SPECT/CT) for preoperative SLN detection in patients with EC.
Keywords: SPECT/CT; endometrial cancer; lymphoscintigraphy; sentinel lymph node